Foreword From Editor - 14th Edition - Andri Yatmo, Yandi (ASEAN Journal of Community Engagement, 2023)
This edition of AJCE brings together discussions on the various roles and effectiveness of research and community engagement programs in strengthening local identity, developing skills, and enhancing quality of life towards a resilient society. Expanding such roles, this issue consists of four research articles, one review article, and three case-based articles. The authors of this edition emerge from the background of language, engineering, economy, policy, education, and health, providing different outlooks and methods in overseeing the processes of community-related programs.